Tinjauan Yuridis Terhadap Praktik Gratifikasi Jual Beli Jabatan Dalam Putusan Pengadilan: Juridical Review of the Practice of Gratification in Position Trading in Court Decisions - Alamanda Nur Mayanti; Hartoyo Hartoyo; Renda Aranggraeni; Muhammad Aqil Fathir (UKInstitute, 2026)
Abstract. This study analyzes the legal review of the criminal act of buying and selling positions by the Regent of Nganjuk Regency based on Decision Number 64/Pid.Sus-TPK/2021/PN.Sby. Buying and selling positions is categorised as bribery that damages the bureaucracy's integrity and state administrators' dignity. The method used is a sociological legal approach, which examines cases based on positive legal principles and their relevance to social conditions. The urgency of this study lies in the importance of enforcing the law against corrupt practices that undermine public trust in the government bureaucracy. The study results show that the defendant, Dupriono, was proven to have given Rp50,000,000.00 to the Regent of Nganjuk, Novi Rahman Hidhayat, to obtain the position of Head of Pace Sub-district. The panel of judges considered that the elements of the criminal offence charged by the Public Prosecutor had been fulfilled, and that the act was committed jointly with other parties. The judges' legal considerations were based on Article 5 paragraph (1) letters a and b, and Article 13 of Law Number 31 of 1999, in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. The result shows that the defendant's actions constituted the criminal act of corruption in the form of gratification of office. This verdict emphasises the importance of enforcing anti-bribery laws as an instrument for maintaining the integrity of the bureaucracy and preventing abuse of authorities. Abstrak. Penelitian ini bertujuan untuk menganalisis tinjauan yuridis terhadap tindak pidana jual beli jabatan oleh Bupati Kabupaten Nganjuk berdasarkan Putusan Nomor 64/Pid.Sus-TPK/2021/PN.Sby. Praktik jual beli jabatan dikategorikan sebagai suap yang merusak integritas birokrasi dan martabat penyelenggara negara. Metode yang digunakan adalah pendekatan yuridis sosiologis, yaitu menelaah kasus berdasarkan asas hukum positif serta relevansinya dengan kondisi sosial. Urgensi penelitian ini terletak pada pentingnya menegakkan hukum terhadap praktik korupsi yang melemahkan kepercayaan publik terhadap birokrasi pemerintahan. Hasil penelitian menunjukkan bahwa terdakwa Dupriono terbukti memberikan uang sebesar Rp50.000.000,00 kepada Bupati Nganjuk, Novi Rahman Hidhayat, untuk memperoleh jabatan sebagai Camat Pace. Majelis hakim menilai bahwa unsur-unsur tindak pidana yang didakwakan Jaksa Penuntut Umum telah terpenuhi, dan perbuatan tersebut dilakukan secara bersama-sama dengan pihak lain. Pertimbangan hukum hakim didasarkan pada Pasal 5 ayat (1) huruf a dan b serta Pasal 13 Undang-Undang Nomor 31 Tahun 1999 jo. Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi. Hasil menunjukkan bahwa perbuatan terdakwa merupakan tindak pidana korupsi berupa gratifikasi jabatan. Putusan ini menegaskan pentingnya penegakan hukum antisuap sebagai instrumen menjaga integritas birokrasi dan mencegah penyalahgunaan wewenang.